Endoplasmic reticulum stress induces cardiac dysfunction through architectural modifications and alteration of mitochondrial function in cardiomyocytes. Issue 2 (3rd August 2018) - Prola, Alexandre; Nichtova, Zuzana; Pires Da Silva, Julie; Piquereau, Jérôme; Monceaux, Kevin; Guilbert, Arnaud; Gressette, Mélanie; Ventura-Clapier, Renée; Garnier, Anne; Zahradnik, Ivan; Novotova, Marta; Lemaire, Christophe
Abstract: Aims: Endoplasmic reticulum (ER) stress has recently emerged as an important mechanism involved in the pathogenesis of cardiovascular diseases. However, the molecular mechanisms by which ER stress leads to cardiac dysfunction remain poorly understood. Methods and results: In this study, we evaluated the early cardiac effects of ER stress induced by tunicamycin (TN) in mice. Echocardiographic analysis indicated that TN-induced ER stress led to a significant impairment of the cardiac function. Electron microscopic observations revealed that ultrastructural changes of cardiomyocytes in response to ER stress manifested extensively at the level of the reticular membrane system. Smooth tubules of sarcoplasmic reticulum in connection with short sections of rough ER were observed. The presence of rough instead of smooth reticulum was increased at the interfibrillar space, at the level of dyads, and in the vicinity of mitochondria. At the transcriptional level, ER stress resulted in a substantial decrease in the expression of the major regulator of mitochondrial biogenesis PGC-1α and of its targets NRF1, Tfam, CS, and COXIV. At the functional level, ER stress also induced an impairment of mitochondrial Ca 2+ uptake, an alteration of mitochondrial oxidative phosphorylation, and a metabolic remodelling characterized by a shift from fatty acid to glycolytic substrate consumption. Conclusions: Our findings show that ER stress induces cytoarchitectural and metabolic alterations in cardiomyocytes and provide evidences that ER stress could represent a primary mechanism that contributes to the impairment of energy metabolism reported in most cardiac diseases.